Phosphorus-based intelligent wave-absorbing agent based on temperature response and method for regulating and controlling wave-absorbing or wave-transmitting performance of phosphorus-based intelligent wave-absorbing agent
By utilizing the temperature-responsive phosphorus-based smart microwave absorbing agent SnP, the reversible phase transition from cubic to tetragonal phase of SnP is achieved, solving the problem of fixed performance of traditional microwave absorbing materials. This enables dynamic adjustment and intelligent response of microwave absorbing materials, promoting the development of stealth and communication technologies.
Patent Information
- Application Number
- CN202511911389.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-17
- Publication Date
- 2026-03-17
AI Technical Summary
Traditional absorbing materials have fixed properties, cannot adapt to complex electromagnetic environment changes, lack intelligent response capabilities, and have poor environmental adaptability.
Using phosphorus-based smart microwave absorber SnP, a reversible phase transition from cubic to tetragonal phase is achieved through temperature induction, dynamically switching the microwave absorption and transmission properties.
This achievement realizes the dynamic, reversible, and adjustable properties of microwave absorbing materials, breaking through the bottleneck of fixed properties of traditional materials and laying the foundation for adaptive stealth and intelligent communication.
Smart Images

Figure CN121674029A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials technology, specifically relating to a temperature-responsive phosphorus-based smart microwave absorber and a method for regulating its microwave absorption or transmission properties. Background Technology
[0002] The technological boom and rapid development of information in the 5G era have brought many benefits to human activities. However, this has also brought about serious electromagnetic pollution that threatens human health and poses significant risks to the safe application of high-frequency electronic devices. To address these issues, electromagnetic wave absorbing materials have emerged. Traditional absorbing materials (such as ferrites, carbon black, and metal powders) are widely used, but they have inherent drawbacks such as: fixed function and single performance: once the material is prepared, its absorption frequency band, absorption intensity, and other properties remain unchanged. They cannot cope with complex electromagnetic threats caused by changes in frequency, polarization, and incident angle; poor environmental adaptability: they cannot dynamically adjust their electromagnetic parameters (dielectric constant, reflection loss) according to changes in the external environment (such as temperature and light) or electromagnetic environment, lacking "intelligent" response capabilities. Driven by the increasingly complex modern electromagnetic environment and the dual demands of military stealth technology for comprehensive, adaptive, and intelligent capabilities, and the complex electromagnetic compatibility challenges faced by civilian communication technologies, a cutting-edge absorbing technology—intelligent absorbing agents—has been developed to overcome the shortcomings of traditional absorbing materials, namely fixed performance and poor environmental adaptability. It represents the inevitable trend of absorbing materials developing from static, passive, and fixed to dynamic, active, and adjustable, and is one of the indispensable key technologies in future high-end equipment and advanced communication systems. Summary of the Invention
[0003] In view of this, the present invention provides a temperature-responsive phosphorus-based smart microwave absorber and a method for regulating its microwave absorption or transmission properties.
[0004] To achieve the above objectives, the present invention provides the following solution: One of the technical solutions of this invention is the application of tin phosphide (SnP) in the preparation of microwave absorbing agents or microwave absorbing materials.
[0005] The second technical solution of the present invention is a temperature-responsive phosphorus-based smart microwave absorber, comprising a SnP mixed phase, a SnP cubic phase, or a SnP tetragonal phase; wherein the SnP mixed phase is a mixture of SnP cubic phase and SnP tetragonal phase.
[0006] The third technical solution of the present invention is a microwave absorbing material, comprising a matrix material and the above-mentioned temperature-responsive phosphorus-based smart microwave absorbing agent.
[0007] The fourth technical solution of the present invention is a method for regulating the microwave absorption or transmission performance of the microwave absorbing agent SnP, wherein the SnP mixed phase or SnP tetragonal phase is induced at high temperature to obtain the SnP cubic phase, thereby realizing the transformation from microwave absorption to microwave transmission. Low-temperature induction of SnP mixed phase or SnP cubic phase yields SnP tetragonal phase, achieving the transformation from wave transmission to wave absorption.
[0008] The fifth technical solution of the present invention is a method for inducing phase transition of SnP, which uses the above-mentioned method to realize the transformation of SnP from tetragonal phase to cubic phase, or the transformation of SnP from cubic phase to tetragonal phase.
[0009] Compared with the prior art, the present invention has the following beneficial effects: This invention utilizes the reversible phase transition of SnP cubic phase ↔ tetragonal phase, enabling the material to switch between the absorbing and transmitting states in situ, reversibly, and without contact, truly endowing the absorbing material with "dynamic, active, and adjustable" intelligent properties, breaking through the bottleneck of traditional materials that are "one-time molding and have fixed performance for life".
[0010] The phase transition conditions of this invention are simple and easy to implement.
[0011] This invention is the first to deeply couple "phase change" with "wave absorption / transmission" functions, laying the material foundation for next-generation adaptive stealth, intelligent communication windows, and reconfigurable electromagnetic shielding, and propelling wave-absorbing materials from the era of "passive stealth" to "cognitive stealth". Attached Figure Description
[0012] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0013] Figure 1 The image shows the X-ray diffraction (XRD) pattern of the mixed-phase SnP powder after passing through a 500-mesh sieve in Example 1.
[0014] Figure 2 The images show the microstructure of the mixed-phase SnP powder after passing through a 500-mesh sieve in Example 1 and the corresponding elemental mapping diagrams. Among them, (a) and (b) are microstructure images at different magnifications, and (c) and (d) are mapping diagrams of P and Sn elements.
[0015] Figure 3 The image shows the XRD pattern of the cubic SnP powder after passing through a 500-mesh sieve in Example 2.
[0016] Figure 4The images show the microstructure of cubic SnP powder after passing through a 500-mesh sieve in Example 2, along with the corresponding mapping diagrams. (a) and (b) are microstructure images at different magnifications, while (c) and (d) are mapping diagrams of P and Sn elements.
[0017] Figure 5 The image shows the XRD pattern of the tetragonal SnP powder after passing through a 500-mesh sieve in Example 3.
[0018] Figure 6 The images show the microstructure of tetragonal SnP powder after passing through a 500-mesh sieve in Example 3 and the corresponding mapping diagrams. Among them, (a) and (b) are microstructure images at different magnifications, and (c) and (d) are mapping diagrams of P and Sn elements.
[0019] Figure 7 XRD patterns of reversible transformation of pure cubic SnP and pure tetragonal SnP.
[0020] Figure 8 The image shows the reflection loss (RL) of the mixed-phase SnP powder after passing through a 500-mesh sieve in Example 1.
[0021] Figure 9 The RL diagram shows the electromagnetic wave absorption performance of cubic and tetragonal SnP phases.
[0022] Figure 10 The diagrams show a comparison of the electromagnetic parameters of the cubic and tetragonal SnP phases. Among them, (a) is a comparison of the real parts of the dielectric constants of the two phases, (b) is a comparison of the imaginary parts of the dielectric constants of the two phases, (c) is a comparison of the attenuation constants of the two phases, and (d) is a comparison of the impedance matching of the two phases. Detailed Implementation
[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0024] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0025] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar to or equivalent to those described herein may be used in the implementation or testing of this invention.
[0026] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0027] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0028] Phosphorus-based materials, as a highly regarded member of the two-dimensional material family, have found applications in electromagnetic wave absorption, energy storage, and biology due to their excellent high conductivity, high energy density, and biocompatibility. SnP, as a metastable phase material, contains both cubic (NaCl-type structure) and tetragonal (tetragonal structure) crystal structures. The tetragonal phase undergoes a phase transition to the cubic phase, becoming a pure cubic phase with wave transmission capability; in low-temperature environments, the cubic phase undergoes a phase transition to the pure tetragonal phase with excellent wave absorption capability. Simultaneously, reversible transformations between the two pure phases occur with changes in ambient temperature. The minimum reflection loss of pure tetragonal SnP is -59.4 dB, with an electromagnetic wave absorption efficiency as high as 99.999%, exhibiting excellent wave absorption performance; the minimum reflection loss of pure cubic SnP is -9 dB, allowing electromagnetic waves to penetrate the material. Therefore, SnP can dynamically adjust its wave absorption and transmission under different environments, achieving intelligent wave absorption. This invention targets the phase of SnP and achieves phase transitions of different phases through temperature induction, providing a temperature-responsive phosphorus-based smart microwave absorbing agent and its preparation method, which helps to realize the application of SnP in smart microwave absorbing materials.
[0029] The first aspect of this invention provides an application of SnP in the preparation of microwave absorbing agents or microwave absorbing materials.
[0030] In a preferred embodiment of the present invention, the SnP is a SnP miscible phase, a SnP cubic phase, or a SnP tetragonal phase; the SnP miscible phase is a mixture of SnP cubic phase and SnP tetragonal phase.
[0031] A second aspect of the present invention provides a temperature-responsive phosphorus-based smart microwave absorber, comprising a SnP mixed phase, a SnP cubic phase, or a SnP tetragonal phase; wherein the SnP mixed phase is a mixture of SnP cubic phase and SnP tetragonal phase.
[0032] A third aspect of the present invention provides a microwave absorbing material, comprising a matrix material and the above-mentioned temperature-responsive phosphorus-based smart microwave absorbing agent.
[0033] In a preferred embodiment of the present invention, the matrix material is paraffin wax, epoxy resin, or polyvinylidene fluoride.
[0034] In some embodiments of the present invention, the microwave absorbing material further includes a microwave transmitting material, a reinforcing material, and / or a functional filler.
[0035] This invention does not impose any particular limitations on the wave-transmitting materials, reinforcing materials, and / or functional fillers, but adopts wave-transmitting materials, reinforcing materials, and functional fillers commonly used by those skilled in the art for wave-absorbing materials.
[0036] The fourth aspect of this invention provides a method for regulating the microwave absorption or transmission performance of the microwave absorbing agent SnP, wherein a SnP mixed phase or SnP tetragonal phase is induced at high temperature to obtain a SnP cubic phase, thereby realizing the transformation from microwave absorption to microwave transmission. Low-temperature induction of SnP mixed phase or SnP cubic phase yields SnP tetragonal phase, achieving the transformation from wave transmission to wave absorption.
[0037] High temperature induces the SnP tetragonal phase to transform into the less conductive SnP cubic phase, allowing electromagnetic waves to pass through, thus achieving wave transmission. Low temperature induces the SnP cubic phase to transform into the more conductive SnP tetragonal phase, which possesses a strong electromagnetic wave absorption capability, thus achieving wave absorption.
[0038] In a preferred embodiment of the present invention, the conditions for high-temperature induction are set as follows: the temperature is increased to 150-250℃ at a rate of 1-5℃ / min and held for 2-12 hours.
[0039] Optionally, the heat-induced insulation time is 2h, 4h, 6h, 8h, 10h and 12h or any value between the two aforementioned values.
[0040] In some embodiments of the present invention, the process further includes natural cooling to room temperature and passing through a 500-mesh sieve after the high-temperature induction is completed; the inert atmosphere is an argon atmosphere. Argon is purged throughout the entire high-temperature induction (annealing) process to isolate oxygen and prevent oxidation of the material. The annealing temperature of 150-250°C is to induce a phase transition from the tetragonal phase (low-temperature phase) to the cubic phase (high-temperature phase) in the miscible SnP. If the annealing temperature is higher than 250°C (e.g., 300°C, 400°C), the phosphorus in SnP will sublimate into amorphous phosphorus due to its inability to withstand higher temperatures, leading to material preparation failure and failure of microwave absorption or transmission control. If the annealing temperature is lower than 150°C (e.g., 100°C), it is insufficient to spontaneously transform the tetragonal phase into the cubic phase, failing to meet the requirements for microwave transmission.
[0041] In a preferred embodiment of the present invention, the conditions for low-temperature induction are set as follows: cooling in an environment of ≤0℃ for 10-30 minutes.
[0042] Optionally, the SnP mixed phase may be cooled in an environment of ≤0°C for 10 min, 20 min, or 30 min, or any value between the two aforementioned values.
[0043] The present invention has experimentally discovered that SnP miscible phase or SnP cubic phase can achieve phase transition to SnP tetragonal phase by low-temperature induction at 0℃; optionally, the ≤0℃ environment can be a liquid nitrogen environment.
[0044] Since cubic SnP is a high-temperature stable material, it will spontaneously transform into a highly ordered (tetragonal) phase in a low-temperature environment, eventually yielding a pure tetragonal SnP crystal sample.
[0045] The process after the low-temperature induction is completed also includes a step of naturally rising to room temperature.
[0046] This invention induces a phase transition in SnP at high and low temperatures, allowing the resulting material to dynamically adjust between absorbing and transmitting electromagnetic waves, thus achieving intelligent wave absorption. By inducing a phase transition from tetragonal to cubic SnP at high temperatures, the weaker conductivity of SnP allows electromagnetic waves to pass through, achieving wave transmission. Conversely, by inducing a phase transition from cubic to tetragonal SnP at low temperatures, the stronger conductivity of SnP results in a powerful electromagnetic wave absorption capability, achieving wave absorption.
[0047] In a preferred embodiment of the present invention, the method for preparing the SnP miscible phase includes the following steps: Sn powder and P powder are mixed and pressed into SnP blocks, then ground and sieved to obtain the SnP mixed phase.
[0048] The molar ratio of Sn powder to P powder is 1:1; the pressing conditions are set as follows: temperature 1000-1300℃, pressure 2-4 GPa, and holding time 2-30 min. The sieving specifically involves passing the powder through a 500-mesh sieve.
[0049] The fifth aspect of the present invention provides a method for inducing a phase transition in SnP, wherein the above-described method is used to achieve the transformation of SnP from a tetragonal phase to a cubic phase, or the transformation of SnP from a cubic phase to a tetragonal phase.
[0050] This invention employs high-temperature annealing to transform the SnP mixed / SnP tetragonal phase into a pure SnP cubic phase, and cooling at ≤0℃ (e.g., liquid nitrogen quenching) to further transform the SnP mixed / SnP cubic phase into a pure SnP tetragonal phase. This process achieves the function of dynamically adjusting electromagnetic wave absorption performance according to temperature changes. The cubic phase is a high-temperature stable material, so its free energy decreases faster than that of the tetragonal phase at high temperatures. When the temperature exceeds a certain critical point (phase transition temperature), the material spontaneously transforms from the tetragonal phase into the cubic phase. At low temperatures, the Gibbs free energy of the tetragonal phase is lower than that of the cubic phase, and the cubic phase spontaneously tends towards a lower, more stable energy state, thus obtaining pure tetragonal SnP.
[0051] Unless otherwise specified, the technical solutions described in this invention are all conventional solutions in the field, and the reagents or raw materials used are all purchased from commercial channels or are publicly available unless otherwise specified.
[0052] The main reagents used in the following examples are shown in the table below:
[0053] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0054] Example 1 This embodiment provides a method for preparing a temperature-responsive phosphorus-based smart microwave absorber (mixable SnP), the steps of which are as follows: Sn and P powders were mixed in a molar ratio of Sn:P = 1:1, and then held at 3 GPa and 1200℃ for 10 min in a six-sided press to obtain SnP bulk material. The SnP bulk material was ground until it could pass through a 500-mesh sieve; the XRD pattern of the resulting mixed-phase SnP powder after sieving is shown below. Figure 1 show; by Figure 1 It can be seen that the miscible SnP in this embodiment has high purity. The scanning electron microscope image and mapping pattern of the miscible SnP powder in this embodiment are shown below. Figure 2 As shown, by Figure 2 It can be seen that the miscible SnP has obvious layering and uniform element distribution.
[0055] Example 2 This embodiment provides a method for preparing a temperature-responsive phosphorus-based smart microwave absorber (cubic phase SnP), the steps of which are as follows: The mixed-phase SnP powder sample prepared in Example 1 was placed in a tube furnace, and the temperature was raised to 200°C within 60 minutes and held for 4 hours. After that, it was naturally cooled to room temperature and passed through a 500-mesh sieve to obtain cubic SnP powder (SnP(Fm-3m)). Before holding, argon gas should be introduced for about 2 minutes to purge the air in the glass tube, and argon gas should be continuously introduced throughout the process until the annealing is completed.
[0056] The XRD pattern of cubic SnP in this embodiment is as follows: Figure 3 As shown; by Figure 3 It can be seen that the cubic SnP in this embodiment has high purity.
[0057] The scanning electron microscope images and mapping spectra of the cubic SnP powder obtained in this embodiment are as follows: Figure 4 As shown; by Figure 4 The cubic SnP phase is clearly layered with uniform elemental distribution. Example 3 This embodiment provides a method for preparing a temperature-responsive phosphorus-based smart microwave absorber (tetragonal SnP), the steps of which are as follows: The mixed-phase SnP powder prepared in Example 1 was cooled in liquid nitrogen for 15 min, then allowed to rise naturally to room temperature, and passed through a 500-mesh sieve to obtain pure tetragonal SnP powder (SnP (14 mm)).
[0058] The XRD pattern of tetragonal SnP in this embodiment is as follows: Figure 5 As shown; by Figure 5 It can be seen that the tetragonal SnP in this embodiment has high purity.
[0059] The scanning electron microscope images and mapping spectra of the tetragonal SnP powder obtained in this embodiment are as follows: Figure 6 As shown, by Figure 6 As can be seen, the tetragonal SnP phase has distinct layers and a uniform elemental distribution; Figure 7 The images show the XRD patterns of the reversible transformation of pure cubic SnP in Example 2 and pure tetragonal SnP in Example 3; Figure 7 It can be seen that at high temperatures, the tetragonal phase spontaneously transforms into the cubic phase, becoming a wave-transmitting material; at low temperatures, the cubic phase spontaneously transforms into the tetragonal phase, becoming a wave-absorbing material.
[0060] Test Example 1 The electromagnetic parameters of the temperature-responsive phosphorus-based smart microwave absorbers (mixed-phase SnP, cubic SnP, and tetragonal SnP) prepared in Examples 1-3 were measured. Test method: The temperature-responsive phosphorus-based smart microwave absorber was uniformly mixed with paraffin at a mass filling ratio of 70%:30% and pressed into a ring-shaped dense body with an inner diameter of 3.04 mm and an outer diameter of 7.00 mm. The dielectric constant and minimum reflection loss value in the frequency range of 2.0~18.0 GHz were measured using a vector network analyzer.
[0061] The measurement results are as follows Figure 8-10 As shown: Figure 8 The image shows the RL diagram of the mixed-phase SnP powder after passing through a 500-mesh sieve in Example 1; from Figure 8 It can be seen that its minimum reflection loss is -22.6dB, indicating that its electromagnetic wave absorption capability is not particularly good.
[0062] Figure 9 The RL diagram shows the electromagnetic wave absorption performance of cubic and tetragonal SnP phases. Figure 10 This is a comparison of the electromagnetic parameters of the cubic and tetragonal SnP phases; where (a) is a comparison of the real parts of the dielectric constant of the two phases, (b) is a comparison of the imaginary parts of the dielectric constant of the two phases, (c) is a comparison of the attenuation constant of the two phases, and (d) is a comparison of the impedance matching of the two phases. Figure 9 and Figure 10 It can be seen that inducing the tetragonal SnP phase to transform into cubic SnP at high temperature allows electromagnetic waves to pass through, achieving wave transmission with a minimum reflection loss of -9dB. Inducing the cubic SnP phase to transform into tetragonal SnP at low temperature results in higher conductivity and stronger electromagnetic wave absorption capabilities, achieving wave absorption with a minimum reflection loss of -59.4dB. These results demonstrate that SnP can dynamically adjust its wave transmission and absorption under different environments, achieving intelligent wave absorption.
[0063] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. Application of SnP in preparation of wave-absorbing agent or wave-absorbing material.
2. Use according to claim 1, characterized in that, The SnP is SnP mixed phase, SnP cubic phase or SnP tetragonal phase; the SnP mixed phase is a mixture of SnP cubic phase and SnP tetragonal phase.
3. A temperature-responsive phosphorus-based smart wave-absorbing agent, characterized by, The SnP includes SnP mixed phase, SnP cubic phase or SnP tetragonal phase; the SnP mixed phase is a mixture of SnP cubic phase and SnP tetragonal phase.
4. A wave-absorbing material, characterized by, The temperature-responsive phosphorus-based intelligent wave-absorbing agent comprises a base material and the temperature-responsive phosphorus-based intelligent wave-absorbing agent in claim 3.
5. The wave-absorbing material according to claim 4, characterized in that, The base material is paraffin, epoxy resin or polyvinylidene fluoride.
6. A method for regulating the wave-absorbing or wave-transmitting performance of a wave-absorbing agent SnP, characterized in that, High-temperature induction is performed on the SnP mixed phase or SnP tetragonal phase to obtain SnP cubic phase, thereby realizing the conversion from wave-absorbing to wave-transmitting. Low-temperature induction is performed on the SnP mixed phase or SnP cubic phase to obtain SnP tetragonal phase, thereby realizing the conversion from wave-transmitting to wave-absorbing.
7. The method of claim 6, wherein the SnP is a wave-absorbing agent. The conditions for high-temperature induction are set as follows: heating at a rate of 1-5 ℃ / min to 150-250 ℃ and holding for 2-12 h.
8. The method for wave-absorbing or wave-transmitting regulation of the wave-absorbing agent SnP according to claim 6, characterized in that, The conditions for low-temperature induction are set as follows: cooling in an environment at ≤0 ℃ for 10-30 min.
9. The method of claim 6, wherein the SnP is a wave-absorbing agent. The preparation method of the SnP mixed phase comprises the following steps: The Sn powder and the P powder are mixed and then pressed into a SnP bulk, followed by grinding and sieving to obtain the SnP mixed phase. The molar ratio of the Sn powder and the P powder is 1:1; the conditions for pressing are set as follows: temperature of 1000-1300 ℃, pressure of 2-4 Pa and holding time of 2-30 min.
10. A method of phase change induction on SnP, characterized by, The method in any one of claims 6-9 is used to realize the conversion from SnP tetragonal phase to SnP cubic phase or the conversion from SnP cubic phase to SnP tetragonal phase.